Design of Gandrung Dance Animated Video for Students with Special Needs - Sri Astuti Iriyani; I Gede Anjas Kharisma Nata; Nahdlatuzzainiyah; Herman Supriantono (Journal of Education Technology, 2026)
Inclusive education guarantees equal access to quality learning for all students, including those with special needs, by providing adaptive learning opportunities that take into account individual differences in physical, intellectual, and emotional abilities. This study aims to develop a prototype of a Gandrung dance animation video as a visual arts learning medium for students with special needs at the Mataram Special School. The media development uses the ADDIE model with a focus on the Analysis, Design, and Development stages. The learning characteristics of students with various disabilities, including blindness, deafness, and mental retardation, are analyzed through observation, interviews with teachers, and studies of the learning environment. The prototype developed was then validated by material and media experts to assess content suitability, movement accuracy, visual quality, and media appeal to users. Limited trials with students showed high levels of response and effectiveness, with scores of 86.7% for content suitability, 85.3% for media quality, and 82.2% from student trials. The results of the study show that the Gandrung dance animation video prototype is not only practical and attractive, but also provides a culturally meaningful learning experience. This media is able to increase student engagement, motivation, creativity, and understanding of local arts and culture, while supporting the optimal implementation of inclusive arts education. These findings confirm that animation-based learning media can be an effective alternative to expand access to arts education for students with special needs and improve the overall quality of their learning experience.